RESULT CLAUSES WITH A PARENTHETICAL CLAUSE IN MACEDONIAN LANGUAGE (Slavic Studies, 2025)
The article analyzes compound sentences with adverbial clauses incorporated in another clause, expressing a consequence in Macedonian. In that sense, it takes into account sentences with at least three clauses in which the third clause is included in the second, the second is subordinate to the first, and the third - to the second, whereas the clause embedded in the one expressing a consequence occurs inparenthetical position. This article examines the complex adverbial meanings arising from those combinations, including the meaning of consequence and the additional components - reason, purpose, condition, time frame, concession. Furthermore, the function of the parenthetical position in regard to the information structure and the interpretation of the meaning is also analysed.
Keywords: consequence; clause; meaning; position; information